Morphological identification of phosphate solubilizing and cellulolytic fungi from mangrove soil under Rhizophora stylosa stands. Issue 1 (November 2021) - Elfiati, D; Delvian; Susilowati, A; Rizki, N W Y; Harahap, A F M; Hidayat, A
Abstract: Mangrove forest is one of the forest ecosystems that can be found in tidal areas. Mangrove forest have ecological, socio-economic benefits for organisms that live in the sea. One of the microorganism that live in mangrove forest is fungus. Therefore, this study aimed to isolate and identify phosphate solubilizing and cellulolytic fungi from mangrove soil. Soil samples were collected from a stands of Rhizophora stylosa in Lubuk Kertang Village, West Brandan District, Langkat Regency, North Sumatra. Soil samples were taken randomly with a dept of 0-20 cm. Isolation of phosphate solubilizing fungi was carried out using Pikovskaya medium and cellulolytic fungi using carboxyl methyl cellulose (CMC) medium. To determine the effectiveness of fungi qualitatively, the phosphate solubility and cellulolytic index were calculated. All isolates obtained were identified morphologically by observing colonies macroscopically and microscopically. This study obtained 12 isolates of phosphate solubilizing and 8 isolates of cellulolytic fungi. Phosphate solubility index ranging from 2.06-2.87 and cellulolytic index of 0.33-3.00. Morphological identifications showed that all isolates of phosphate solubilizing fungi belonged to the genus Aspergillus, while all isolates of cellulolytic fungi belonged to the genus Chaetomium .